Determinant factors of technical succesfull on captive breeding of yellow-crested cockatoo – (Cacatua sulphurea sulphurea) - Setiana, Toni; Masy'ud, Burhanuddin; Hernowo, Jarwadi Budi (Media Konservasi, 2018)
Technically, key indators of bird captive breeding successfullness are marked by successful of reproduction, low rate of mortality  and well growing and development offspring in captivity. There are many technical factors of captivity that are allegedly to be determinant of birds captive breeding successfulness. Based on these reason, the study  was aimed to: (1) analyize and synthesize the technical aspects of yellow-crested cockatoo captive breeding that are applied in several captivity sites, and (2) analyze the technical factors as determinant of the yellow-crested cockatoo captive breeding successfulness. The study was conducted in March-May 2015 in five bird captive breeding sites in Bogor, Bandung and Jakarta. Data was collected through field observations by following bird maintenance activities in captivity and interviews, then collected data were analyzed by qualitative descriptive. Technical factors determinant analysis was carried out using the PCA (Principle Component Analysis) method. The results showed that from the five captive breeding sites, two units (40%) were classified as successful birds captive breeding sites, two units (40%) were classified as unsuccessful namely successfully laying eggs but had not hatched, and one unit (20%) was unsuccessful captive breeding (unable to lay eggs). Technically, successful captivity of the yellow-crested cockatoo minimally is maintained in a square cage with at least 1.5 x 3 x 3 m3 size, equipped with enrichment in the form of palm trees, wood of bird perch, nesting box,  food and water container. Feed given in the form of grains (corn, beans, kuaci), fruits (bananas, papaya) and vegetables, as well as the additional food in the form of porridge. In general, captivity management that are applied at the sample site can be stated to be quite good and successful, marked by the success of bird breeding and no bird deaths were found. There are two determinant factors of the technical success of captivity that must receive attention, namely feed factors, health care factors and medical measures. Keywords captive breeding, determinant factors, reproduction and mortality,  succesfull technique, yellow-crested cockatoo